The Effect of Service Quality on Student Satisfaction and Student Loyalty at Madrasah Aliah Negeri Pekanbaru - Rahmadani Hidayat; Nusyirwan Nusyirwan; Safrizal Safrizal (Dinasti International Journal of Economics, Finance & Accounting, 2023)
The research team at Madrasah Aliyah Negeri in Pekanbaru set out to examine the connection between the quality of service provided to students and their level of satisfaction and loyalty to the institution. Three hundred and twelve students from two Pekanbaru public Madrasah Aliyah schools participated in the study. Student satisfaction and loyalty are treated as endogenous variables in this study, while service quality is used as an exogenous variable. Amos 24, Microsoft Excel 2013, and Structural Equation Modeling (SEM) were used for data analysis. The findings indicated that the quality of services provided contributed to happy students. Both service quality and customer satisfaction have a positive impact on retention rates among students.